PENGARUH LINGKUNGAN KERJA, KOMUNIKASI KERJA, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN KOPERASI SIMPAN PINJAM JASA PUSAT PEKALONGAN - Talenta Dinda Majid, 14.05.51.0205; Suko Priyono, Bambang (Students Journal of Economic and Management, 2018)
This study aims to determine the effect of work environment, work communication, work motivation and work discipline to employee performance of Savings and Loans Cooperative Center Pekalongan. The population in this study were 146 employeesat of Savings and Loans Cooperative Center Pekalongan. The Sampleused judgmen sampling technic with 102 respondents. The data used primary data and secondary data, analysed using linear regression . The results showed that the work environment, work communication, work motivation, and work discipline had a positive and significant effect on employee performance of Savings and Loans Cooperative Center Pekalongan. From these results can be concluded that a good work environment, a good work communication high work motivation, and high working discipline will improve employee performance of Savings and Loans Cooperative Center Pekalongan.Keywords : work environment , work communication, work motivation , work discipline and employee performance